Dialectics of Forgiveness between Ethnic Communities for West Kalimantan Harmony - Marta, Rustono Farady; Fernando, Joshua (Universitas Semarang, 2020)
West Kalimantan has a history of inter-ethnic conflicts, and the process of reconciliation has been continued until today in order to create a complete peace. This present study uses the qualitative method of explorative case study from the perspective of Arendt's Political Forgiveness Theory to analyze the process of individual forgiveness in the ongoing reconciliation process. The results indicate that the dialectics of forgiveness practices that occur individually cannot be achieved completely due to several factors, but the presence of the West Kalimantan Children's Forum, the Madurese Family Association, the Alliance for Peace and Transformation, and the Dayakology Institute stimulates the emergence of collective forgiveness for the past inter-ethnic conflicts in the younger generation in West Kalimantan. The findings suggest that sustainable justice is the main solution that will enable all ethnic groups to live in harmony.